Evaluasi Kinerja Jaringan Irigasi Curah Melalui Simulasi Hidrolis Menggunakan Epanet 2.0 - Helena Novitasari Lasol; Yuli Suharnoto; Dadang Ridwan; Marasi Deon Joubert (Jurnal Irigasi, 2014)
Sprinkler irrigation network could be a good investment when designed, installed, maintained and managed well. But manually calculation consumes much time and gives rise to human error. Therefore, this study aims to evaluate the performance of sprinkler irrigation using secondary data and the data was analyzed by using simulation of EPANET 2.0 software. This study was conducted on irrigation network in the village of Tenilo, Gorontalo and the villages of Akar-akar, NTB. The simulation resulted the average pressure at both locations was excess of the recommended optimum pressure 40 m, but it was not excess the maximum recommended pressure 65 m. The variation pressure on each location were 2.82 m and 9.35 m. Debit issued by sprinkler was also nearing discharge plan 9.11 liters/second. The velocity of the flow both locations was not different much. It was less than maximum allowable speed 3 m/s, it meant that the network was safe from abrasion and water hammer on a pipe. Based on the results, simulation sprinkler irrigation network installed in the village of Tenilo and the villages of Akar-akar have met the criteria of hydraulic limitation design of sprinkler irrigation.